Effect of oral 25% dextrose on pain relief in newborn infants undergoing venepuncture - Raju, H. N. Yashwanth; Sudha, Rudrappa; N., Shwetha B. (International Journal of Contemporary Pediatrics, 2020)
Background: Aim of this study was to study effect of oral 25% dextrose for pain relief in newborns undergoing venepuncture. Methods: This is a case control study conducted in NICU, Cheluvamba hospital attached to Mysore medical college and research institute during the period between September 2018 to November 2018. Babies with gestational age between 34 to 40 weeks of gestation who had clinical indication for blood sampling were included in the study. Neonates who are critically ill, suffered perinatal asphyxia and having congenital anomalies were excluded from the study. Hundred newborn babies admitted to NICU who had clinical indication for blood sampling were enrolled in the study. Study population were divided into 2 groups, dextrose (cases) and non-dextrose group (controls). The data analysis included gestational age, postnatal age, weight, sex, heart rate, oxygen saturation, crying time and behavioural pain assessment. Results: Mean pain score, crying time and heart rate at 5 minutes of venepuncture were studied in both the groups. Mean pain score in dextrose group was 2.68 and in non-dextrose group was 7.18 with significant p value of 0.0062. Mean crying time in dextrose group was 8.98 minutes and in non-dextrose group was 42 minutes with significant p value of 0.001. Mean heart rate in dextrose group was 142 beats/minute and in non-dextrose group was 146bpm with p value of 0.08. Conclusions: Pain in the newborns should be recognised and adequately treated. Lingual 25% dextrose can be used as safe and effective analgesia in neonates undergoing minor invasive procedures like venepuncture.